Preservation of Indian Mackerel (Rastrelliger kanagurta) Using Fish Protein Hydrolysate Based Bioactive Edible Coating Incorporated with Chitosan and Clove Oil - Kannaiyan, Sathish Kumar; Bindu J; Elavarasan K; Amjad K. Balange; Narasimhamurthy L (Fishery Technology, 2023)
The study was conducted to develop ready to disperse bioactive edible coating (BEC) powder using fish protein hydrolysate added with chitosan and clove oil and evaluate their bio-preservation effect in mackerel fillets during refrigerated storage. Mackerel fillet’s quality was measured by monitoring the changes in the microbial growth (mesophilic and psychrotrophic bacterial counts), biochemical quality parameters (pH, TBARS, TVB-N, TMA and PV), and sensory quality during 18 days of storage. The initial mesophilic and psychrotrophic bacterial count of mackerel fillets were 4.51 ± 0.37 and 3.68 ± 0.25 log CFU/g respectively and a significant increase was observed in control samples compared to 10 % and 20 % BEC solution coated samples during storage. Control samples exceeded the acceptable limit on day 9, whereas the samples coated with 10 % and 20 % BEC solution exceeded the limit on 15th and 18th day of storage, respectively. In biochemical quality analysis, the pH value increased steadily in control sample than the BEC solution coated samples. Lowest TBARS value was measured in 20 % BEC treated sample (1.72 ± 0.05 mg MDA/kg) followed by 10 % BEC solution treated sample (1.94 ± 0.09 mg MDA/kg) at the end of storage, while control sample exceeded the acceptable limit (2.22 ± 0.12 mg MDA/kg) on 12th day, which revealed that BEC solutions effectively prolonged the shelf life of mackerel fillets. The sensory values gradually decreased in all the samples corresponding to the microbial and biochemical quality changes. The study revealed that the FPH based BEC powder incorporated with chitosan and clove oil showed an excellent biopreservation effect in mackerel fillets and could have broad potential applications in food products as a natural bio-preservative.